William Barton Rogers and the Idea of MIT - Angulo, A. J. (Johns Hopkins University Press, 2009)
Winner, 2009 Outstanding Book Award, History of Education SocietyWinner, 2009 Richard Slatten Prize for Excellence in Virginia Biography, Virginia Historical SocietyConceptual founder of the Massachusetts Institute of Technology, William Barton Rogers was a highly influential scientific mind and educational reformer of the nineteenth century. A. J. Angulo recounts the largely unknown story of one man's ideas and how they gave way to the creation of one of America's premier institutions of higher learning. MIT's long tradition of teaching, research, and technological innovation for real-world applications is inexorably linked to Rogers' educational philosophy. Emphasizing the "useful arts"-a curriculum of specialized scientific study stressing theory and practice, innovation and functionality-Rogers sought to revolutionize standard educational practices of the day. Controversial in an era typified by a generalist approach to teaching the sciences, Rogers' model is now widely emulated by institutions throughout the world. Exploring the intersection of Rogers' educational philosophy and the rise of technical institutes in America, this biography offers a long-overdue account of the man behind MIT.